Investigation of the Effects of Teeth Clenching Due to Weight Training on Oral Health - Sang Min Lee; Eun Chae Lee; Juwon Gong; Chae Eun Jang; Young Sun Hwang (The Korean Society of Dental Hygiene Science, 2024)
Background: As interest in health increases, the number of people engaging in weight training to enhance muscle strength and muscle mass is on the rise. High-intensity weight training has been reported to induce tooth clenching habits, leading to tooth damage and temporomandibular joint (TMJ) abnormalities. Consequently, it is essential to investigate the impact of weight training accompanied by tooth clenching on oral health and to develop guidelines based on these findings. Methods: The study included male participants aged 25 years and older, comprising 15 non-exercisers and 15 professional fitness trainers who have been engaged in weight training for over 5 years. Data were collected using a self-administered questionnaire to gather information on age, exercise experience, total weight lifted in three major weight training exercises (deadlift, bench press, and squat), and teeth clenching habits. Additionally, examinations for tooth cracks and fractures, TMJ noise and pain, maximum mouth opening, occlusal force, and occlusal contact area were conducted. Results: Compared to non-exercisers, professional fitness trainers who have been engaged in weight training for over 5 years exhibited a higher prevalence of teeth clenching habits. While there were no significant differences between the two groups in occlusal contact area and the extent of tooth fractures, there were significant differences in occlusal force and the degree of tooth cracks. Furthermore, unlike joint noise and TMJ pain, the maximum mouth opening was significantly reduced in professional fitness trainers compared to non-exercisers. Conclusion: Our study suggests that the continuation of high-intensity exercise, which induces teeth clenching habits, may cause tooth damage and TMJ disorders.